Immune checkpoint blockade in advanced cutaneous squamous cell carcinoma: What do we currently know in 2020? - Wessely, Anja; Steeb, Theresa; Leiter, Ulrike; Garbe, Claus; Berking, Carola; Heppt, Markus (International Journal of Molecular Sciences, 2020)
Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer that predominantly arises in chronically sun-damaged skin. Immunosuppression, genetic disorders such as xeroderma pigmentosum (XP), exposure to certain drugs and environmental noxae have been identified as major risk factors. Surgical removal of cSCC is the therapy of choice and mostly curative in early stages. However, a minority of patients develop locally advanced tumors or distant metastases that are still challenging to treat. Immune checkpoint blockade (ICB) targeting CTLA-4, PD-L1 and PD-1 has tremendously changed the field of oncological therapy and especially the treatment of skin cancers as tumors with a high mutational burden. In this review, we focus on the differences between cSCC and cutaneous melanoma (CM) and their implications on therapy, summarize the current evidence on ICB for the treatment of advanced cSCC and discuss the chances and pitfalls of this therapy option for this cancer entity. Furthermore, we focus on special subgroups of interest such as organ transplant recipients, patients with hematologic malignancies, XP and field cancerization.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Cemiplimab; Cutaneous squamous cell carcinoma; Immune checkpoint blockade; Pembrolizumab; Skin cancer